An exploration into how family functioning impacts adolescent mental health during lockdown : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology at Massey University, New Zealand - Ram, Avita (Massey University, 2022)
The mental health of adolescents is found to be impacted by many factors, with one of the most predominant being the way their families function. However with the ongoing COVID-19 pandemic and subsequent lockdowns being a reasonably new phenomena, understanding this relationship in the context of lockdown has not currently been investigated, yet remains necessary. Thus this qualitative research underpinned by critical realism, aimed to be the first to understand the impact of family functioning on adolescent mental health during lockdown, namely the two New Zealand lockdowns. Seven families that consisted of an adolescent in New Zealand were recruited via social media to participate in semi-structured interviews. Data from these interviews were recorded and transcribed to then conduct thematic analysis. Four key themes were identified which were; (1) adolescent roles changed during lockdown which benefited their mental health, (2) poorer problem solving during lockdown negatively impacted adolescent mental health, (3) increased emotional responsiveness allowed for greater emotional support during lockdown which benefited adolescent mental health and (4) emphasis of family values during lockdown benefited and maintained adolescent mental health. These findings highlight that family functioning did change during lockdown, which more often than not benefited adolescent mental health. This may then have important implications in dealing with the repercussions of the current lockdowns as well as providing insight into possible future lockdowns when specifically dealing with the mental health of adolescents in New Zealand. However no research is without its limitations, which will be discussed along with recommendations for future research which focus on encouraging further research within this area.
Keywords: 520304 Health psychology